Greenhouse Gas Emissions and Mitigation Measures within the Forestry and Other Land Use Subsector in Malawi - Edward Missanjo; Henry Kadzuwa (International Journal of Forestry Research)
Analysing past trends of greenhouse gas (GHG) emissions remains indispensable to the understanding of current GHG emissions, thereby enabling prediction of future emissions as well as development of their mitigative pathways. This study quantified GHG emissions within the Forest and Other Land Use (FOLU) subsector in Malawi for the period 2011 to 2020. Results indicate that Malawi’s GHG emissions in the FOLU subsector fluctuated but decreased by 0.84 MtCO2e (13%) from 2011 to 2020, averaging to −1.3% annually. The GHG emissions of different categories within the subsector were highly significant (p<0.001) and contributed the highest (99.72%) of the total variation. Forestland contributed the highest (74%) of the subsector category emissions, followed by biomass burning (19%). The uncertainties for the estimated GHG emissions were low (<15%). This shows that the estimated GHG emissions within the FOLU subsector were significantly minimised. Notable interventions that have abated the emissions include afforestation and natural/assisted regeneration; protection and conservation of protected areas through the REDD+ mechanism; establishment of seed banks for raising drought-tolerant tree species; and breeding of fast-growing and drought-tolerant tree species; as well as screening of disease and pest-resistant species and promotion of biological control.